Anaerobic microbial community response to methanogenic inhibitors 2‐bromoethanesulfonate and propynoic acid. Issue 4 (14th March 2016) - Webster, Tara M.; Smith, Adam L.; Reddy, Raghav R.; Pinto, Ameet J.; Hayes, Kim F.; Raskin, Lutgarde
Abstract: Methanogenic inhibitors are often used to study methanogenesis in complex microbial communities or inhibit methanogens in the gastrointestinal tract of livestock. However, the resulting structural and functional changes in archaeal and bacterial communities are poorly understood. We characterized microbial community structure and activity in mesocosms seeded with cow dung and municipal wastewater treatment plant anaerobic digester sludge after exposure to two methanogenic inhibitors, 2‐bromoethanesulfonate (BES) and propynoic acid (PA). Methane production was reduced by 89% (0.5 mmol/L BES), 100% (10 mmol/LBES), 24% (0.1 mmol/LPA), and 95% (10 mmol/LPA). Using modified primers targeting the methyl‐coenzyme M reductase ( mcrA ) gene, changes in mcrA gene expression were found to correspond with changes in methane production and the relative activity of methanogens. Methanogenic activity was determined by the relative abundance of methanogen 16S rRNA cDNA as a percentage of the total community 16S rRNA cDNA. Overall, methanogenic activity was lower when mesocosms were exposed to higher concentrations of both inhibitors, and aceticlastic methanogens were inhibited to a greater extent than hydrogenotrophic methanogens. Syntrophic bacterial activity, measured by 16S rRNA cDNA, was also reduced following exposure to both inhibitors, but the overall structure of the active bacterial community was not significantly affected. Abstract : This manuscript reports a comprehensive approach to characterizing the effects of commonly used methanogenesis inhibitors on an anaerobic microbial community. We use mock and environmental communities and target two genes using DNA‐ and RNA‐based methods. Results from Illumina sequencing of the 16S rRNA gene, 16S rRNA cDNA, mcrA gene, and mcrA transcript cDNA highlight shifts in both methanogenic archaeal activity and syntrophic bacterial activity.